Literature review : hubungan aktivitas fisik dengan kejadian hipertensi - Dhaniang, Natasya; Kahanjak, Donna Novina; Permatasari, Silvani (Barigas: Jurnal Riset Mahasiswa, 2023)
Hypertension, also known as high blood pressure, is a worldwide health issue. Hypertension is a condition in which the systolic and diastolic blood pressures rise above the usual limit. Lack of physical activity as a risk factor for hypertension needs more attention because this factor is a factor that can be modified with minimal effort and cost.  Understanding the tendency of the relationship between physical activity and the incidence of hypertension. The literature review uses a systematic review approach, data sources, data sources from original articles in the Pubmed.gov and Google Scholar databases with the keywords relationship, physical activity, and hypertension. There were 21 journals that met the inclusion criteria and data quality analysis. Synthesis of data using the SPIDER method. Based on the results of a literature review it was found that in the twenty-four journals analyzed, there were 18 (86%) journals that stated they were related and 3 (14%) stated otherwise. Individuals with lower physical activity tend to have a higher risk of hypertension and the factors that influence it include diet, age, nutritional status, family history of hypertension, smoking to routine health checks.